ESTETIKA TARI BANGILUN TRI KARYA TAMA DI DUSUN JENGKOL KABUPATEN TEMANGGUNG - Maryani, Avina Budi; Wiyoso, Joko (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study aims to analyze the aesthetics of Bangilun Dance in the Tri Karya Tama art group located in Jengkol Hamlet, Dlimoyo Village, Ngadirejo District, Temanggung Regency. The main focus of this research is to reveal the value of beauty contained in the presentation of dance, both in terms of movement, visual, and musical accompaniment. The method used in this study is qualitative descriptive with an aesthetic approach. Data collection techniques were carried out through participatory observation, in-depth interviews with local managers and artists and documentation studies. The results of the study show that the aesthetics of Bangilun Dance in the Tri Karya Tama art community are reflected through the combination of wiraga, wirama, and wirasa elements. Visually, the use of unique costumes such as sunglasses and colonial-style attributes creates a distinctive folk identity. In terms of movement, this dance displays energetic dynamics that are in harmony with the rhythm of flying music (tambourine) with religious nuances. This aesthetic uniqueness not only serves as a spectacle, but also as a means of binding social solidarity and preserving the cultural identity of the people of Jengkol Hamlet in the midst of modernization.